2017
DOI: 10.3390/md15120385
|View full text |Cite
|
Sign up to set email alerts
|

The Cladophora glomerata Enriched by Biosorption Process in Cr(III) Improves Viability, and Reduces Oxidative Stress and Apoptosis in Equine Metabolic Syndrome Derived Adipose Mesenchymal Stromal Stem Cells (ASCs) and Their Extracellular Vesicles (MV’s)

Abstract: This study investigated in vitro effects of freshwater alga Cladophora glomerata water extract enriched during a biosorption process in Cr(III) trivalent chromium and chromium picolinate on adipose-derived mesenchymal stromal stem cells (ASCs) and extracellular microvesicles (MVs) in equine metabolic syndrome-affected horses. Chemical characterisation of natural Cladophora glomerata was performed with special emphasis on: vitamin C, vitamin E, total phenols, fatty acids, free and protein-bound amino acids as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 44 publications
3
25
0
Order By: Relevance
“…), polyphenols (196±8 mg/100 g of d.m. ), free and protein-bound amino acids (e.g., Ala, Glc, Val, Leu, Ile, Asn, Asp, Gln, Glu, Lys, Arg, His, Phe, Tyr, Trp, Ser, Thr, Met, Cys, Pro) and fatty acids [ 18 ]. Fatty acids present in the biomass of C .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…), polyphenols (196±8 mg/100 g of d.m. ), free and protein-bound amino acids (e.g., Ala, Glc, Val, Leu, Ile, Asn, Asp, Gln, Glu, Lys, Arg, His, Phe, Tyr, Trp, Ser, Thr, Met, Cys, Pro) and fatty acids [ 18 ]. Fatty acids present in the biomass of C .…”
Section: Resultsmentioning
confidence: 99%
“…The SEM-EDX investigation allows the examination in details the surface concentration and distribution of Cr(III), Mn(II) and Mg(II) ions in the natural and enriched Cladophora glomerata . In our and other previous research it was shown, that SEM-EDX becomes a valuable tool for a precise investigation of the elemental composition, as well as distribution of elements in different biomasses [ 6 , 18 , 39 ]. In the present study, the SEM-EDX elemental analysis revealed the increased quantity of Mg, Cr, as well as Mn in the course of biosorption process in Cladophora glomerata biomass ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The biomass of freshwater Cladophora glomerata is a rich source of primary and secondary metabolites, such as amino acids and proteins, carbohydrates, carotenoids, minerals, vitamins, fatty acids, sterols, terpenes etc. [43,44]. These compounds can be useful in the stimulation of plant growth.…”
Section: Introductionmentioning
confidence: 99%